VD_FINDINFO HC / 2017 / 1182 vom 11. Januar 2018 - VD Tribunal cantonal (2018)
ACTION EN CONSTATATION, ACTION EN EXÉCUTION, COURTAGE, RECONNAISSANCE DE DETTE | 319 al. 1 CO, 394 CO, 414 CO, 88 CPC (CH)